Genomic Characteristics of Desulfonema ishimotonii Tokyo 01T Implying Horizontal Gene Transfer Among Phylogenetically Dispersed Filamentous Gliding Bacteria - Watanabe, Miho; Kojima, Hisaya; Umezawa, Kazuhiro; Fukui, Manabu (Frontiers in Microbiology, 2019)
Desulfonema ishimotonii strain Tokyo 01T is a filamentous sulfate-reducing bacterium isolated from a marine sediment. In this study, the genome of this strain was sequenced and analyzed with a focus on gene transfer from phylogenetically distant organisms. While the strain belongs to the class Deltaproteobacteria, hundreds of proteins encoded in the genome showed the highest sequence similarities to those of organisms outside of the class Deltaproteobacteria, suggesting that more than 20% of the genome is putatively of foreign origins. Many of these proteins had the highest sequence identities with proteins encoded in the genomes of filamentous bacteria, including giant sulfur oxidizers of the orders Thiotrichales, cyanobacteria of various genera, and uncultured bacteria of the candidate phylum KSB3. As mobile genetic elements transferred from phylogenetically distant organisms, putative inteins were identified in the GyrB and DnaE proteins encoded in the genome of strain Tokyo 01T. Genes involved in DNA recombination and repair were enriched in comparison to the closest relatives in the same family. Some of these genes were also related to those of organisms outside of the class Deltaproteobacteria, suggesting that they were acquired by horizontal gene transfer from diverse bacteria. The genomic data suggested significant genetic transfer among filamentous gliding bacteria in phylogenetically dispersed lineages including filamentous sulfate reducers. This study provides insights into the genomic evolution of filamentous bacteria belonging to diverse lineages, characterized by various physiological functions and different ecological roles.